Monitoring The Effectiveness In Eliminating The Trace Presence Of AOZ (Furazolidone Derivative) Residue In Penaeus Monodon And Its Products Undergoing Different Processing Regimes [RM666.F82 T161 2008 f rb]. - Tan, Thuan Chew (2008)
Pihak berkuasa Malaysia telah mengharamkan penggunaan furazolidon (salah satu daripada nitrofuran utama yang ada) dalam haiwan ternakan.